THE INFULENCE OF EASE OF USE AND FACILITY TOWARDS CUSTOMER SATISFACTION ON FINTECH DIGITAL PAYMENT - Lantang, Andhy Philip; Pangemanan, Sifrid S.; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
This study aims to determine the level of customer satisfaction with the use of financial technology in the field of digital payments for students of the economics and business faculty of the University of Sam Ratulangi based on the effect of ease of use and the facilities provided in the service. This type of research is descriptive analysis approach. By using quantitative research methods. The sample taken for this study amounted to 100 respondents. The sampling technique used is non-probability sampling with purposive sampling technique and the data collection instrument is a questionnaire which is run through Google Form. Furthermore, testing and data analysis was carried out using SPSS 26 software. The results found in this study showed that simultaneously Ease of use  and Facility  had a significant positive effect on the level of Customer Satisfaction  with an of 50,397. In addition, Ease of Use and facility each partially has a positive and significant influence on customer satisfaction. Adjusted R Square value obtained from the test results of the coefficient of determination  of 0.510 explains that 51% of customer satisfaction can be explained by ease of use and facility. While the remaining 49% is explained by other variables not examined in this study. Keywords: ease of use, facility, customer satisfaction, digital payment.